Production of biodiesel from used cooking oil - Yunus, Rosli Mohd; Isha, Ruzinah; Zainal Abidin, Sumaiya; Abdul Rasid, Ruwaida (2012)
Biodiesel is a cleaner burning diesel replacement fuel processed from natural, renewable derived from biological sources such as used vegetable oils and animal fats . The type of process that used to produce biodiesel is transesterification. Transesterification is the commonly process that used widely compare to other process. This process is important to convert free fatty acid (FFA) in oil to ester. In this research, waste cooking oil is used as raw material with Potassium hydroxide (KOH) as catalyst and methanol as a solvent. The reaction has been done in laboratory and pilot plant for comparison. The parameter that been investigated were reaction time and catalyst concentration while reaction temperature was fixed at 65°C. The purity of methyl ester content in biodiesel is measured by Gas Chromatography. The exhaust emissions of biodiesel produced were evaluated by combustion test using Gas Combustion Unit. Results indicate that the higher conversion was obtained by waste cooking oil used as the raw material with 97.4% compared to RBD palm oil which is 98.2%. Biodiesel produced from WCO gives less exhaust emission of CO and CO2 compared to commercial diesel thus contributed to the reduction of greenhouse gas that effect the global warming. Finally, the biodiesel sample was tested on several parameters which are the yield, thin layer chromatography (TLC) and moisture content to ensure its meet the standard requirement of ASTM D6751 for biodiesel B100.